A method for preparing an n-TOPCon battery with thinned back poly
By forming a loose PSG with laser light and cleaning and removing the polysilicon layer and the second poly-Si layer, the efficiency problem caused by the poly-Si thickness on the back of the n-TOPCon battery is solved, achieving more efficient battery performance.
Patent Information
- Application Number
- CN202411492810.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The poly-Si thickness on the back of the existing n-TOPCon batteries leads to parasitic absorption loss, and too small the thickness will cause a risk of burn-through, resulting in a decrease in battery efficiency.
The laser acts on the non-contact area of the back of the battery to form a loose porous structure. Then, the polysilicon layer and the second poly-Si under the porous structure are removed by HF and alkali washing, and the silicon oxide layer is retained to achieve the technical purpose of thinning.
It effectively reduces the poly-Si thickness of the back contact area, reduces the risk of burn-through, improves battery efficiency, and improves the double-sided rate and power generation power of the battery.
Smart Images

Figure CN119153583B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells, and in particular relates to a method for preparing an n-TOPCon cell with thinned back poly. Background Art
[0002] The n-TOPCon cell is a tunneling oxide passivation contact solar cell based on an N-type silicon substrate. It has been widely studied and applied on a large scale in recent years. At present, the tunneling oxide passivation structure of the n-TOPCon cell can be realized by the following methods: The first method is to realize SiO x / poly-Si; the second is PECVD to prepare SiO2 / a-Si(n); the third is to achieve SiO by PEALD x Growth, and then PECVD to prepare a-Si(n); PECVD to prepare SiO x Then a-Si(n) was prepared by plate-type PVD.
[0003] The thickness of the poly-Si on the back of a conventional TOPCon cell is generally greater than 70nm, and thicker poly has greater parasitic absorption losses; when the thickness of the poly-Si is ≤60nm, the contact becomes poor, there is a risk of burn-through, and metal-induced recombination increases, resulting in reduced cell efficiency. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method of an n-TOPCon battery with thinned back poly, which uses laser to act on the dense PSG in the non-contact area on the back of the battery, so that the PSG in the non-contact area forms a loose porous structure, and the PSG is washed away during HF cleaning and winding plating, and then the de-plated polysilicon layer and the second layer of poly-Si covered by the PSG with a porous structure are washed away by alkaline washing, and a layer of silicon oxide is retained, thereby achieving the technical purpose of thinning the back of the n-TOPCon battery, and retaining the poly-Si in the contact area, reducing the risk of battery burn-through, and improving battery efficiency.
[0005] The above technical objectives of the present invention are achieved through the following technical solutions:
[0006] The present invention provides a method for preparing an n-TOPCon battery with a thinned back poly layer, comprising the following steps:
[0007] Adopt N-type silicon wafer, double-sided texturing, forming a pyramid structure for surface light trapping;
[0008] B diffusion is carried out on the front side to form a PN junction;
[0009] HF cleaning is used on the back side to remove BSG on the back side and around, and alkaline polishing is used to remove B wrapping;
[0010] The PECVD method is used to prepare a stacked structure including a tunneling oxide passivation structure on the back side. The stacked structure obtained after annealing is: the first SiO x / The first poly-Si(n + ) / Second SiO x / The second poly-Si(n + );
[0011] P diffusion is performed on the back side to obtain PSG;
[0012] Laser is used to act on the PSG in the non-contact area on the back side, so that the PSG in the non-contact area becomes loose and pores appear, thus forming loose PSG;
[0013] Chain HF cleaning is used to remove the PSG on the front and side surfaces and expose the polysilicon layer under the wrap-around plating while cleaning the PSG;
[0014] By using alkaline washing, the polysilicon layer under the plating on the front and side is removed, and at the same time, the alkaline solution passes through the pores of the loose PSG to remove the second poly-Si (n + ) and the second SiO x Remove at the same time; specifically, with the front BSG facing downward, chain HF cleaning is used to remove the surrounding PSG, while retaining part of the BSG on the front;
[0015] Then use alkaline washing and tank de-plating cleaning to remove the first SiO2 around the periphery (without PSG). x / The first poly-Si(n + ) / Second SiO x / The second poly-Si(n + ) / PSG structure, while removing the second SiO x / The second poly(n + ) Outer layer structure, the non-laser area (outer PSG) retains the first SiO x / First poly-Si(n+) / Second SiO x / The second poly-Si(n+) / PSG structure achieves the effect of thinning poly;
[0016] Aluminum oxide passivation is applied on the front side and / or the back side to form an aluminum oxide layer;
[0017] Silicon nitride passivation is performed on the front and / or back sides to form SiN x membrane;
[0018] The main grid lines and auxiliary grid lines are screen-printed on the front and back sides respectively, and ohmic contacts are formed by sintering. Light injection improves passivation and light decay, and LECO laser enhances passivation contact performance.
[0019] Among them, during the alkali washing process, the concentration of the alkali solution is determined according to the following formula:
[0020] ;
[0021] Where d1 is the thickness of the polysilicon layer deposited by the coating, in nm;
[0022] d2 is the second poly-Si(n + ) and SiO x The thickness of the layer in nm;
[0023] k1 and k2 are the wrapped polysilicon layer and the second poly-Si (n + ) and SiO x The cleaning rate constant of the layer, in nm / min;
[0024] C is the concentration of alkali solution in %.
[0025] In order to ensure the performance of the battery, in this embodiment, the cleaning is completed in one step, and the second poly-Si (n + ) and the second SiO x The lower layer of the layer, but to ensure that the polysilicon layer under the coating is completely cleaned, so the above formula is used to balance the cleaning speed of the two materials by adjusting the alkali solution concentration C, so that they can be cleaned at the same time t, and the second poly-Si (n + ) and the second SiO x The layer below the layer.
[0026] Furthermore, k1 and k2 are obtained by fitting the data.
[0027] Furthermore, the fitting method of k1 and k2 is as follows:
[0028] Take the alkali solution concentration C, cleaning time t, thickness change d and corresponding cleaning rate V under different experimental conditions. The experimental results include at least the polysilicon layer (V1) and the second poly-Si (n + ) and SiO x The cleaning rate of layer (V2) is calculated based on the experimental data, and the calculated cleaning rate data is recorded together with the corresponding alkali solution concentration C and other experimental conditions (such as temperature and time) to form a data set;
[0029] The cleaning rate constants k1 and k2 were fitted, and the relationship between the cleaning rate V and the alkali solution concentration C and other factors was established;
[0030] With alkali solution concentration C and time t as input features and cleaning rates V1 and V2 as target variables, the relationship between V and C is directly fitted by the least squares method to obtain k1 and k2.
[0031] Further, B diffusion is performed on the front side to form a PN junction, including the following steps:
[0032] After the primary B diffusion, the laser SE forms a selective emitter and oxidizes.
[0033] Specifically, the primary B diffusion junction depth is 0.22±0.1μm and the peak concentration is 1×10 20 atoms / cm 3 , square resistance is 130±5Ω / sq;
[0034] Laser SE forms a selective emitter, and the peak concentration drops to 1.4×10 19 atoms / cm 3 , the junction depth increases to 1.2±0.22μm, and the square resistance is 100±5Ω / sq;
[0035] Oxidation reduces square resistance and forms a BSG protective film. + The peak concentration in the region is 3.2×10 18 atoms / cm 3 , junction depth is 0.75±0.05μm, p ++ The peak concentration in the region is 5.4×10 18 atoms / cm 3 , junction depth is 1.4±0.2μm, p + The square resistance of the area is 380±10Ω / sq, and the contact area p ++ The square resistance of the area is 240±5Ω / sq.
[0036] Furthermore, the resistivity of N-type silicon wafers is 0.5~2Ω.cm, and the minority carrier lifetime is >10ms.
[0037] Furthermore, in the stacked structure, the first SiO x The thickness of the first poly-Si(n + ) thickness is 0~50nm, the second SiO x The thickness of the second poly-Si(n + ) thickness is 0~50nm. x / poly(n+) can also be prepared by LPCVD, PECVD, PEALD + PECVD, and PECVD + PVD methods.
[0038] Furthermore, the first poly-Si(n + ) and the second poly-Si(n + ) has a peak concentration of (2~3)×10 20 atoms / cm 3 , the inflection point concentration is (8~9)×10 18 atoms / cm 3 .
[0039] Furthermore, the thickness of PSG is 4~40nm.
[0040] Furthermore, the laser is a green laser or a purple laser, the spot size is 100±5μm, the scanning speed is 20±2m / s, and the laser power is 30~50W.
[0041] Furthermore, the porosity of loose PSG is 5% to 15%;
[0042] Among them, the porosity of micropores accounts for 5~20%;
[0043] The porosity ratio of the micropores is controlled by the spot overlap ratio of the laser.
[0044] In the present invention, the selection of laser power is particularly important. If the laser power is too high, the PSG will be too loose, resulting in damage to the first poly-Si (n + ); If the laser power is too low, the PSG cannot be loosened, resulting in the inability of the alkali solution to penetrate the PSG during cleaning, and the inability to completely remove the second poly-Si(n + ) and the second SiO x , the thinning effect is lost.
[0045] Therefore, the present invention controls the power of the laser to 30-50W, the porosity of the loose PSG to 5%-15%, and the porosity of the micropores to 5-20%, so that the alkali solution can penetrate into the loose PSG and the second poly-Si(n + ) and the second SiO x Complete cleaning and protect the first SiO layer below x / The first poly-Si(n + ) is not damaged.
[0046] Furthermore, the calculation formula of the spot overlap rate is as follows:
[0047] ;
[0048] Where, O is the spot overlap ratio, the unit is 1;
[0049] β is the laser action constant, with the unit being 1;
[0050] θ is the porosity ratio of micropores, with the unit being 1.
[0051] Furthermore, β is determined according to the laser power, the spot area and the scanning speed. In this specific embodiment, the spot size is selected to be 100±5μm, the scanning speed is 20±2m / s, and the laser power is 30~50W. Therefore, according to data fitting, β is taken between 0.2~0.3, preferably 0.25.
[0052] Furthermore, the thickness of the aluminum oxide layer is 3 nm.
[0053] In summary, the present invention has the following beneficial effects:
[0054] (1) The thinning method provided by the present invention achieves excellent passivation and contact performance through high square resistance on the front side and SE superimposed LECO technology;
[0055] (2) The thinning method provided by the present invention makes the back contact area SiO x / poly(n + )1 / SiO x / poly(n + )2 The structure effectively reduces the metal J0, and the non-contact area uses thin poly, or no poly structure, which reduces the metal J0 while improving the passivation performance;
[0056] (3) Greatly improve the efficiency of the battery, thin the poly in the non-contact area on the back, greatly improve the bifaciality of the battery, and increase the power generation capacity of the module. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 A flow chart of the method for preparing the poly thinning on the back side of an n-TOPCon battery provided by the present invention;
[0058] Figure 2 A schematic diagram of the structure of the n-TOPCon battery provided by the present invention;
[0059] Figure 3 This is the ECV curve diagram of Example 1 of the present invention.
[0060] Reference numerals
[0061] 1. P ++ 2. SiN x ; 3. AlO x ; 4. P + ; 5. The first SiO x ; 6. The first poly-Si (n + ); 7. SiN x; 8. Second SiO x ; 9. The second poly-Si (n + ). DETAILED DESCRIPTION
[0062] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, a preparation method of a back-side poly-thinned n-TOPCon battery proposed in the present invention, its specific implementation method, characteristics and effects are described in detail as follows.
[0063] The present invention provides a method for preparing a back-side poly-thinned n-TOPCon cell, such as Figure 1 As shown, the following steps are included:
[0064] S1, using N-type silicon wafer, double-sided texturing, forming a pyramid structure for surface light trapping;
[0065] S2, B diffusion is performed on the front side to form a PN junction;
[0066] S3, use HF cleaning on the back to remove BSG on the back and around, and use alkali polishing to remove B wrap;
[0067] S4, using PECVD method to prepare a stacked structure including a tunneling oxide passivation structure on the back side, and the stacked structure obtained after annealing is: the first SiO x / The first poly-Si(n + ) / Second SiO x / The second poly-Si(n + ) / PSG;
[0068] S5, using laser to act on the PSG in the non-contact area, so that the PSG in the non-contact area is loosened, pores appear, and loose PSG is formed;
[0069] S6, using chain HF cleaning to remove the PSG plated on the front and side surfaces and expose the plated polysilicon layer;
[0070] S7, use alkali washing to remove the polysilicon layer on the front and side surfaces, and at the same time allow the alkali solution to pass through the pores of the loose PSG to remove the second poly-Si (n + ) and the second SiO x Remove;
[0071] S8, using aluminum oxide passivation on the front and / or back surface to form an aluminum oxide layer;
[0072] S9, perform silicon nitride passivation on the front and / or back to form SiN x membrane;
[0073] S10, the main grid lines and auxiliary grid lines are formed by screen printing on the front and back sides respectively, and ohmic contacts are formed by sintering. Light injection improves passivation and light attenuation, and LECO laser enhances passivation contact performance.
[0074] The structure of the obtained n-TOPCon battery is as follows Figure 2 shown.
[0075] In some preferred embodiments, the resistivity of the N-type silicon wafer is 0.5-2Ω.cm, and the minority carrier lifetime is >10ms;
[0076] Among them, during the alkali washing process, the concentration of the alkali solution is determined according to the following formula:
[0077] ;
[0078] Where d1 is the thickness of the polysilicon layer deposited by the coating, in nm;
[0079] d2 is the second poly-Si(n + ) and SiO x The thickness of the layer in nm;
[0080] k1 and k2 are the wrapped polysilicon layer and the second poly-Si (n + ) and SiO x The cleaning rate constant of the layer, in nm / min;
[0081] C is the concentration of alkali solution in %.
[0082] In some preferred embodiments, k1 and k2 are obtained by fitting the data.
[0083] In some preferred embodiments, the fitting method is as follows:
[0084] Take the alkali solution concentration C, cleaning time t, thickness change d and corresponding cleaning rate V under different experimental conditions. The experimental results include at least the polysilicon layer (V1) and the second poly-Si (n + ) and SiO x The cleaning rate of layer (V2) is calculated based on the experimental data, and the calculated cleaning rate data is recorded together with the corresponding alkali solution concentration C and other experimental conditions (such as temperature and time) to form a data set;
[0085] The cleaning rate constants k1 and k2 were fitted, and the relationship between the cleaning rate V and the alkali solution concentration C and other factors was established;
[0086] With alkali solution concentration C and time t as input features and cleaning rates V1 and V2 as target variables, the relationship between V and C is directly fitted by the least squares method to obtain k1 and k2.
[0087] In some preferred embodiments, k1 and k2 are 0.13 and 0.39, respectively.
[0088] In some preferred embodiments, B diffusion is performed on the front side to form a PN junction, the junction depth of the PN junction is 0.7±0.1μm, and the peak concentration is 1.42±0.2×10 19 atoms / cm 3 The square resistance of the contact area is 100~400Ω / sq, and the square resistance of the non-contact area is 200~600Ω / sq.
[0089] In some preferred embodiments, B diffusion is performed on the front side to form a PN junction, including the following steps:
[0090] After the primary B diffusion, the laser SE forms a selective emitter and oxidizes.
[0091] Further, B diffusion is performed on the front side to form a PN junction; the steps include:
[0092] The primary B diffusion junction depth is 0.22±0.1μm and the peak concentration is 1×10 20 atoms / cm 3 , square resistance is 130±5Ω / sq;
[0093] Laser SE forms a selective emitter, and the peak concentration drops to 1.4×10 19 atoms / cm 3 , the junction depth increases to 1.2±0.22μm, and the square resistance is 100±5Ω / sq;
[0094] Oxidation, the peak concentration of the p+ region after oxidation is 3.2×10 18 atoms / cm 3 , the junction depth is 0.75±0.05μm, and the peak concentration in the p++ region is 5.4×10 18 atoms / cm 3 The junction depth is 1.4±0.2μm, the square resistance of the p+ region is 380±10Ω / sq, and the square resistance of the contact area p++ region is 240±5Ω / sq.
[0095] In some preferred embodiments, HF cleaning is performed on the back side to remove BSG on the back side and around, and alkaline polishing is performed to remove B wrapping, and the resulting tower base size is 11±2 μm.
[0096] In some preferred embodiments, in the stacked structure, the first SiO x The thickness of the first poly-Si(n + ) thickness is 0~50nm, the second SiO xThe thickness of the second poly-Si(n + ) thickness is 0~50nm.
[0097] In some preferred embodiments, the first poly-Si(n + ) and the second poly-Si(n + ) has a peak concentration of (2~3)×10 20 atoms / cm 3 , the inflection point concentration is (8~9)×10 18 atoms / cm 3 .
[0098] In some preferred embodiments, the thickness of PSG is 4-40 nm.
[0099] In some preferred embodiments, the laser is a green laser or a purple laser with a power of 30-50 W and an action time of 100-300 s.
[0100] In some preferred embodiments, the porosity of loose PSG is 5% to 15%, and the porosity of micropores accounts for 5% to 20% of the total porosity; wherein the porosity ratio of micropores is controlled by the spot overlap rate of the laser.
[0101] Exemplarily, the calculation formula of the spot overlap rate is as follows:
[0102] ;
[0103] Where, O is the spot overlap ratio, the unit is 1;
[0104] β is the laser action constant, with the unit being 1;
[0105] θ is the porosity ratio of micropores, with the unit being 1.
[0106] It is understandable that the spot overlap rate affects the energy distribution of the laser irradiation area, which in turn affects the size, shape and distribution of the micropores; if the spot overlap rate is too low, the area covered by the laser on the material surface is reduced, resulting in insufficient energy distribution of each spot, and the laser energy cannot effectively penetrate the material, resulting in insufficient formation of micropores. It can also lead to uneven micropore formation areas, insufficient number of pores or unsatisfactory morphology, and inability for the alkali solution to penetrate into the second poly-Si (n + ) and the second SiO x When the spot overlap rate is too high, the laser inputs too much energy in the same area, causing the material to overheat or melt locally, and the macropores formed become too large or out of control, and even directly cause the PSG to melt and be directly thinned, unable to provide a tortuous channel for the alkali solution, resulting in the first poly-Si (n + ) is damaged.
[0107] Therefore, in this specific embodiment, by controlling the spot overlap rate, the energy input in the same local area is controlled to ensure the pore ratio of the micropores, thereby achieving the requirements of this specific embodiment without damaging the first poly-Si (n + ), and can completely remove the dipoly-Si(n + ) and the second SiO x purpose.
[0108] Exemplarily, β is determined based on laser power, spot area and scanning speed. In this specific embodiment, the spot size is 100±5μm, the scanning speed is 20±2m / s, and the laser power is 30~50W. Therefore, according to data fitting, β is between 0.2~0.3, preferably 0.25.
[0109] In this embodiment, if the power of the laser is too high, the PSG will be too loose, resulting in damage to the first poly-Si (n + ); If the laser power is too low, the PSG cannot be loosened, resulting in the inability of the alkali solution to penetrate the PSG during alkali washing, and the inability to completely remove the second poly-Si(n + ) and the second SiO x , the thinning effect is lost.
[0110] In some preferred embodiments, the thickness of the aluminum oxide layer is 3 nm.
[0111] Example 1
[0112] A method for preparing an n-TOPCon cell with a thinned back poly layer, comprising the following steps:
[0113] S1. Use N-type silicon wafers with a resistivity of 0.5Ω.cm and a minority carrier lifetime of >10ms to remove damage and form a pyramid structure for surface light trapping;
[0114] S2, the front B diffuses to form a PN junction, the B diffusion junction depth is 1.0μm, and the peak concentration is 7.46×10 18 atoms / cm 3 , square resistance is 301Ω / sq;
[0115] S3, HF cleaning on the back to remove BSG on the back and surrounding areas, alkali polishing on the back to remove B wrapping, the tower base size is 11μm;
[0116] S4, back PECVD + annealing to prepare the first SiO x / The first poly-Si(n + ) / Second SiOx / The second poly-Si(n + ) / PSG stacked structure, in which the first SiO x The thickness of the first poly-Si(n + ) has a thickness of 40 nm, and the second SiO x The thickness of the second poly-Si(n + ) thickness is 40nm, two layers of poly-Si(n + ) had a peak concentration of 3×10 20 atoms / cm 3 , the inflection point concentration is 8×10 18 atoms / cm 3 , the thickness of PSG is 10 nm;
[0117] S5, use green laser to act on the non-laser area of PSG to make PSG loose;
[0118] S6, chain HF cleaning to remove the surrounding PSG and de-plating cleaning;
[0119] S7, use alkali washing to remove the polysilicon layer on the front and side surfaces, and at the same time allow the alkali solution to pass through the pores of the loose PSG to remove the second poly-Si (n + ) and the second SiO x Remove;
[0120] S8, front aluminum oxide passivation, aluminum oxide thickness is 3nm;
[0121] S9, front / back silicon nitride passivation;
[0122] S10, front / back screen printing forms main / sub grid lines, sintering forms ohmic contact, light injection improves passivation and light decay, LECO laser enhances passivation contact performance.
[0123] Among them, the spot size is selected as 100μm, the scanning speed is 20m / s, the laser power is 30W, the porosity of loose PSG is 8%, and the porosity of micropores accounts for 10%. According to the formula, the overlap rate of the laser spot is 42%.
[0124] Among them, according to the formula, during alkaline washing, the alkali concentration is 4.84%.
[0125] Example 2
[0126] A method for preparing an n-TOPCon cell with a thinned back poly layer, comprising the following steps:
[0127] S1. Use N-type silicon wafers with a resistivity of 0.5Ω.cm and a minority carrier lifetime of >10ms to remove damage and form a pyramid structure for surface light trapping;
[0128] S2, the front B diffuses to form a PN junction, the B diffusion junction depth is 1.0μm, and the peak concentration is 7.46×10 18 atoms / cm 3 , square resistance is 301Ω / sq;
[0129] S3, HF cleaning on the back to remove BSG on the back and surrounding areas, alkali polishing on the back to remove B wrapping, the tower base size is 11μm;
[0130] S4, back PECVD + annealing to prepare the first SiO x / The first poly-Si(n + ) / Second SiO x / The second poly-Si(n + ) / PSG stacked structure, in which the first SiO x The thickness of the first poly-Si(n + ) thickness is 42nm, the second SiO x The thickness of the second poly-Si(n + ) thickness is 42nm, the first poly-Si(n + ) had a peak concentration of 2×10 20 atoms / cm 3 , the first poly-Si(n + ) had a peak concentration of 3×10 20 atoms / cm 3 The inflection point concentration is 8×10 18 atoms / cm 3 , the thickness of PSG is 10 nm;
[0131] S5, use green laser to act on the non-laser area of PSG to make PSG loose;
[0132] S6, chain HF cleaning to remove the surrounding PSG and de-plating cleaning;
[0133] S7, use alkali washing to remove the polysilicon layer on the front and side surfaces, and at the same time allow the alkali solution to pass through the pores of the loose PSG to remove the second poly-Si (n + ) and the second SiO x After cleaning, the non-laser area on the back retains the first SiO x / The first poly-Si(n + ) / Second SiO x / The second poly-Si(n + ) structure, the laser area is the contact area with the first SiO x / The first poly-Si(n + )structure;
[0134] S8, front aluminum oxide passivation, aluminum oxide thickness is 3nm;
[0135] S9, front / back silicon nitride passivation;
[0136] S10, front / back screen printing forms main / sub grid lines, sintering forms ohmic contact, light injection improves passivation and light decay, LECO laser enhances passivation contact performance.
[0137] Among them, the spot size is selected as 105μm, the scanning speed is 22m / s, the laser power is 35W, the porosity of loose PSG is 10%, and the porosity of micropores is 15%. According to the calculation, the spot overlap rate is 65%.
[0138] Among them, according to the formula, during alkaline washing, the alkali concentration is 4.88%.
[0139] Example 3
[0140] A method for preparing an n-TOPCon cell with a thinned back poly layer, comprising the following steps:
[0141] S1. Use N-type silicon wafers with a resistivity of 0.5Ω.cm and a minority carrier lifetime of >10ms to remove damage and form a pyramid structure for surface light trapping;
[0142] S2, the primary B diffusion junction depth is 0.22μm, and the peak concentration is 1×10 20 atoms / cm 3 , square resistance is 130Ω / sq;
[0143] S3, laser SE forms a selective emitter, and the peak concentration drops to 1.4×10 19 atoms / cm 3 , the junction depth increases to 1.2μm, and the square resistance is 100Ω / sq;
[0144] S4, oxidation, after oxidation, the peak concentration of the p+ region is 3.2×10 18 atoms / cm 3 , the junction depth is 0.75μm, and the peak concentration in the p++ region is 5.4×10 18 atoms / cm 3 , the junction depth is 1.4μm, the p+ region square resistance is 380Ω / sq, and the contact region p++ region square resistance is 240Ω / sq;
[0145] S5, HF cleaning on the back to remove BSG on the back and surrounding areas, alkali polishing on the back to remove B wrapping, the tower base size is 11±2μm;
[0146] S6, back PECVD + annealing to prepare the first SiO x / First poly-Si(n+) / Second SiO x / The second poly-Si(n+) / PSG stacked structure, in which the first SiO x The thickness of the first poly-Si(n + ) has a thickness of 30 nm, and the second SiO x The thickness of the second poly-Si(n + ) thickness is 40nm, the first poly-Si(n + ) had a peak concentration of 2×10 20 atoms / cm 3 , the first poly-Si(n + ) had a peak concentration of 3×10 20 atoms / cm 3 The inflection point concentration is 8×10 18 atoms / cm 3 , the thickness of PSG is 10 nm;
[0147] S7, use green laser to act on the non-laser area of PSG to make PSG loose;
[0148] S8, chain HF cleaning to remove the surrounding PSG and de-plating cleaning;
[0149] S9, use alkali washing to remove the polysilicon layer on the front and side surfaces, and at the same time allow the alkali solution to pass through the pores of the loose PSG to remove the second poly-Si (n + ) and the second SiO x At the same time, after cleaning, the non-laser area on the back side retains the first SiO x / The first poly-Si(n + ) / Second SiO x / The second poly-Si(n + ) / PSG structure, the laser area is the contact area with the first SiO x / The first poly-Si(n + )structure;
[0150] S10, front aluminum oxide passivation, aluminum oxide thickness is 3nm;
[0151] S11, front / back silicon nitride passivation;
[0152] S12, front / back screen printing forms main / sub grid lines, sintering forms ohmic contact, light injection improves passivation and light decay, LECO laser enhances passivation contact performance.
[0153] Among them, the spot size is selected as 105μm, the scanning speed is 22m / s, the laser power is 35W, the porosity of loose PSG is 10%, and the porosity of micropores is 5%. According to the calculation, the spot overlap rate is 22%.
[0154] Among them, according to the formula, during alkaline washing, the alkali concentration is 4.24%.
[0155] Example 4
[0156] A method for preparing an n-TOPCon cell with a thinned back poly layer, comprising the following steps:
[0157] S1. Use N-type silicon wafers with a resistivity of 0.5Ω.cm and a minority carrier lifetime of >10ms to remove damage and form a pyramid structure for surface light trapping;
[0158] S2, the primary B diffusion junction depth is 0.22μm, and the peak concentration is 1×10 20 atoms / cm 3 , square resistance is 130Ω / sq;
[0159] S3, laser SE forms a selective emitter, and the peak concentration drops to 1.4×10 19 atoms / cm 3 , the junction depth increases to 1.2μm, and the square resistance is 100Ω / sq;
[0160] S4, oxidation, after oxidation, the peak concentration of the p+ region is 3.2×10 18 atoms / cm 3 , the junction depth is 0.75μm, and the peak concentration in the p++ region is 5.4×10 18 atoms / cm 3 , the junction depth is 1.4μm, the p+ region square resistance is 380Ω / sq, and the contact region p++ region square resistance is 240Ω / sq;
[0161] S5, HF cleaning on the back to remove BSG on the back and surrounding areas, alkali polishing on the back to remove B wrapping, the tower base size is 11μm;
[0162] S6, back PECVD + annealing to prepare the first SiO x / The first poly-Si(n + ) / Second SiO x / The second poly-Si(n +) / PSG stacked structure, in which the first SiO x The thickness of the first poly-Si(n + ) has a thickness of 20 nm, and the second SiO x The thickness of the second poly-Si(n + ) thickness is 50nm, the first poly-Si(n + ) had a peak concentration of 2×10 20 atoms / cm 3 , the first poly-Si(n + ) had a peak concentration of 3×10 20 atoms / cm 3 The inflection point concentration is 8×10 18 atoms / cm 3 , the thickness of PSG is 10 nm;
[0163] S7, use green laser to act on the non-laser area of PSG to make PSG loose;
[0164] S8, chain HF cleaning to remove the surrounding PSG and de-plating cleaning;
[0165] S9, use alkali washing to remove the polysilicon layer on the front and side surfaces, and at the same time allow the alkali solution to pass through the pores of the loose PSG to remove the second poly-Si (n + ) and the second SiO x At the same time, after cleaning, the non-laser area on the back retains the first SiO x / The first poly-Si(n + ) / Second SiO x / The second poly-Si(n + ) / PSG structure, the laser area is the contact area with the first SiO x / The first poly-Si(n + )structure;
[0166] S10, front aluminum oxide passivation, aluminum oxide thickness is 3nm;
[0167] S11, front / back silicon nitride passivation;
[0168] S12, front / back screen printing forms main / sub grid lines, sintering forms ohmic contact, light injection improves passivation and light decay, LECO laser enhances passivation contact performance.
[0169] In the example, the spot size is 105μm, the scanning speed is 22m / s, the laser power is 35W, the porosity of loose PSG is 10%, and the porosity of micropores is 15%. According to the calculation, the spot overlap rate is 65%. According to the formula, the alkali concentration is 3.56% during alkali washing.
[0170] Comparative Example 1
[0171] BL group prepared conventional TOPCon by PECVD method:
[0172] N-type silicon wafers with a resistivity of 0.5Ω.cm and a minority carrier lifetime of >10ms are used for texturing to remove damage and form a pyramid structure for surface light trapping;
[0173] The front B diffuses to form a PN junction, the B diffusion junction depth is 0.7μm, and the peak concentration is 1.42×10 19 atoms / cm 3 , square resistance is 125Ω / sq;
[0174] The back side is cleaned with HF to remove the BSG on the back side and around, and the back side is polished with alkali to remove the B wrapping, and the tower base size is 11μm;
[0175] The tunneling oxide passivation structure was prepared by back PECVD method, where the thickness of the tunneling oxide layer was 1.5 nm and the a-Si(n + ) thickness is 80nm; annealing forms poly-Si(n + ) has a peak concentration of 3×10 20 atoms / cm 3 , the inflection point concentration is 8×10 18 atoms / cm 3 ;
[0176] Front HF cleaning to remove PSG and de-wrap plating;
[0177] The front side is aluminum oxide passivated, and the aluminum oxide thickness is 3nm;
[0178] Front / back silicon nitride passivation;
[0179] The main / sub-gate lines are formed by screen printing on the front / back sides, ohmic contacts are formed by sintering, light injection improves passivation and light decay, and LECO laser enhances passivation contact performance.
[0180] Comparative Example 2
[0181] A method for preparing a back-side poly-thinned n-TOPCon battery is the same as Example 3, except that, the spot size is selected to be 105 μm, the scanning speed is 22 m / s, the laser power is 35 W, the porosity of the loose PSG is 10%, and the spot overlap rate is 42%.
[0182] Comparative Example 3
[0183] A method for preparing an n-TOPCon battery with thinned back poly is the same as Example 3, except that, the spot size is selected to be 105 μm, the scanning speed is 22 m / s, the laser power is 35 W, the porosity of the loose PSG is 10%, and the spot overlap rate is 12%.
[0184] Comparative Example 4
[0185] A method for preparing an n-TOPCon battery with thinned back poly is the same as that of Example 3, except that during alkali washing, the alkali concentration is 3%.
[0186] Comparative Example 5
[0187] A method for preparing an n-TOPCon battery with thinned back poly is the same as that of Example 3, except that during alkali washing, the alkali concentration is 6%.
[0188] Performance Testing
[0189] Taking the performance of the conventional TOPCon battery prepared in Comparative Example 1 as a benchmark, the battery structures obtained in Examples 1 to 4 and the Comparative Example were tested. Figure 3 The ECV curve diagram of Example 1 is shown, and the other test results are shown in Table 1.
[0190] Example Voc[mV] FF[%] Eta[%] Example 1 2.1 0.30 0.12 Example 2 3.2 0.31 0.17 Example 3 3.1 0.35 0.21 Example 4 2.6 0.22 0.16 Comparative Example 1 1.8 0.33 0.13 Comparative Example 2 1.9 0.34 0.11 Comparative Example 3 1.2 0.36 0.08 Comparative Example 4 1.1 0.38 0.14
[0191] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been presented as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing an n-TOPCon cell with a thinned back poly layer, characterized in that: The steps include: Adopt N-type silicon wafer, double-sided texturing, forming a pyramid structure for surface light trapping; B diffusion is carried out on the front side to form a PN junction; HF cleaning is used on the back side to remove BSG on the back side and around, and alkaline polishing is used to remove B wrapping; The PECVD method is used to prepare a stacked structure including a tunneling oxide passivation structure on the back side. The stacked structure obtained after annealing is as follows from bottom to top: the first SiO x / The first poly-Si(n + ) / Second SiO x / The second poly-Si(n + ) / PSG; Laser is used to act on the PSG in the non-contact area on the back side, so that the PSG in the non-contact area becomes loose and pores appear, thus forming loose PSG; Chain HF cleaning is used to remove the PSG on the front and side surfaces and expose the polysilicon layer under the wrapping. Alkaline washing is used to remove the polysilicon layer on the front and side surfaces. At the same time, the alkali solution passes through the pores of the loose PSG to remove the second poly-Si (n + ) and the second SiO x Remove at the same time; Aluminum oxide passivation is applied on the front side and / or the back side to form an aluminum oxide layer; Silicon nitride passivation is performed on the front and / or back sides to form SiN x membrane; The main grid lines and auxiliary grid lines are screen-printed on the front and back sides respectively, and ohmic contacts are formed by sintering. Light injection improves passivation and light decay, and LECO laser enhances passivation contact performance. Among them, during the alkali washing process, the concentration of the alkali solution is determined according to the following formula: ; Where d1 is the thickness of the polysilicon layer deposited by the coating, in nm; d2 is the second poly-Si(n + ) and SiO x The thickness of the layer in nm; k1 and k2 are the wrapped polysilicon layer and the second poly-Si (n + ) and SiO x The cleaning rate constant of the layer, in nm / min; C is the concentration of alkali solution, the unit is %; The porosity of the loose PSG is 5% to 15%; Among them, the porosity of micropores accounts for 5~20%; The porosity ratio of the micropores is controlled by the spot overlap ratio of the laser; The calculation formula of spot overlap rate is as follows: ; Where, O is the spot overlap ratio, the unit is 1; β is the laser action constant, with the unit being 1; θ is the porosity ratio of micropores, with the unit being 1.
2. The method for preparing a n-TOPCon cell with a thinned back poly layer according to claim 1, characterized in that: The k1 and k2 are obtained by fitting the data.
3. The method for preparing a n-TOPCon cell with a thinned back poly layer according to claim 1, characterized in that: The method of performing B diffusion on the front side to form a PN junction comprises the following steps: After the primary B diffusion, the laser SE forms a selective emitter and oxidizes.
4. The method for preparing a n-TOPCon cell with a thinned back poly layer according to claim 3, characterized in that: The primary B diffusion junction depth is 0.22±0.1μm and the peak concentration is 1×10 20 atoms / cm 3 , the square resistance is 130±5Ω / sq.
5. The method for preparing a n-TOPCon cell with a thinned back poly layer according to claim 3, characterized in that: Laser SE forms a selective emitter, and the peak concentration drops to 1.4×10 19 atoms / cm 3 , the junction depth increases to 1.2±0.22μm, and the square resistance is 100±5Ω / sq.
6. The method for preparing a n-TOPCon cell with a thinned back poly layer according to claim 3, characterized in that: Oxidation reduces the square resistance and forms a BSG protective film. After oxidation, the peak concentration of the p+ region is 3.2×10 18 atoms / cm 3 , the junction depth is 0.75±0.05μm, and the peak concentration in the p++ region is 5.4×10 18 atoms / cm 3 , the junction depth is 1.4±0.2μm, the p+ region square resistance is 380±10Ω / sq, and the contact region p ++ The square resistance of the area is 240±5Ω / sq.
7. The method for preparing a n-TOPCon cell with a thinned back poly layer according to claim 1, characterized in that: In the stacked structure, the first SiO x The thickness of the first poly-Si(n + ) thickness is 0~50nm, the second SiO x The thickness of the second poly-Si(n + ) thickness is 0~50nm.
8. The method for preparing a n-TOPCon cell with a thinned back poly layer according to claim 1, characterized in that: The thickness of the PSG is 4-40 nm.
9. The method for preparing a n-TOPCon cell with a thinned back poly layer according to claim 1, characterized in that: The laser is a green laser or a purple laser, the spot size is 100±5μm, the scanning speed is 20±2m / s, and the laser power is 30~50W.
Citation Information
Patent Citations
TOPCon battery and preparation method thereof
CN117995944A
Solar cell and preparation method thereof
CN118380508A